One Health Probiotics as Biocontrol Agents: One Health Tomato Probiotics - Natalya Harutyunyan; Almagul Kushugulova; Narine Hovhannisyan; Astghik Pepoyan (Plants, 2022)
Tomato (Lycopersicon esculentum) is one of the most popular and valuable vegetables in the world. The most common products of its industrial processing in the food industry are juice, tomato paste, various sauces, canned or sun-dried fruits and powdered products. Tomato fruits are susceptible to bacterial diseases, and bacterial contamination can be a risk factor for the safety of processed tomato products. Developments in bioinformatics allow researchers to discuss target probiotic strains from an existing large number of probiotic strains for any link in the soil–plant–animal-human chain. Based on the literature and knowledge on the “One Health” concept, this study relates to the suggestion of a new term for probiotics: “One Health probiotics”, beneficial for the unity of people, animals, and the environment. Strains of Lactiplantibacillus plantarum, having an ability to ferment a broad spectrum of plant carbohydrates, probiotic effects in human, and animal health, as well as being found in dairy products, vegetables, sauerkraut, pickles, some cheeses, fermented sausages, fish products, and rhizospheric soil, might be suggested as one of the probable candidates for “One Health” probiotics (also, for “One Health—tomato” probiotics) for the utilization in agriculture, food processing, and healthcare.